OCURRENCE OF COCCINELLIDS IN A SPONTANEOUS PLANT CONYZA CANADENSIS (L.) - Cristina Nunes dos Santos, Amanda (2021)
The objective of this work to register the occurrence and the influence of meteorological factors in the species of coccinelids, associated to the self- grown plant Conyza canadensis (L.). The work was performed during the period between March, 23 rd and July, 31 st, in 2019, in the vegetable garden of the Olericulture Department at IFSULDEMINAS, Campus Machado. The ladybugs were collected weekly in the weed plants, which were later forwarded to the Biology lab, where they were sorted and submitted to the identification. It has been found the species of Cycloneda sanguinea, Harmonia axyridis, Hippodamia convergens and larvae of ladybirds. Temperature and humidity influenced in the occurrence of ladybugs in the plants of C. canadensis.